Smoking and other health factors in patients with head and neck cancer. (August 2022) - McCarter, Kristen; Baker, Amanda L.; Wolfenden, Luke; Wratten, Chris; Bauer, Judith; Beck, Alison K.; Forbes, Erin; Carter, Gregory; Leigh, Lucy; Oldmeadow, Christopher; Britton, Ben
Abstract: Background: Information on smoking and other health factors in head and neck cancer (HNC) patients throughout treatment, follow-up and survivorship is limited. This study explores patterns of multiple health factors during radiotherapy (RT) and naturalistic long-term follow-up in a convenience sample of patients with HNC. Methods: Smoking, alcohol use and depression were measured at baseline, 4 and 12 weeks post RT for a sub-group of 99 patients who participated in a randomised controlled trial and completed long-term follow-up. These factors plus healthy eating, physical activity and fatigue are also reported from the long-term follow-up component. Smoking was measured by self-report and biochemically, whilst all other variables were by self-report. Where variables were assessed at multiple time points logistic mixed effects regression models determined within-person changes over time. Results: There were important discrepancies between self-reported (4–7%) and biochemically verified (13–29%) rates of smoking. Rates of smoking and hazardous alcohol intake were significantly increased at follow-up compared to baseline. Depression rates were observed to be higher at end of RT compared to baseline. At long-term follow-up, fatigue was common and co-occurred with suboptimal healthy eating and hazardous alcohol use. Conclusion: Clinically important levels of smoking and alcohol consumption post RT in this sample suggest possible targets for intervention beyond treatment into long-term follow-up of patients. Highlights: Actual smoking rates may be higher than self-reported in head and neck cancer. Multiple health factors should be assessed and considered for intervention targets. Health factor intervention should include longer-term support beyond treatment.